Designing New York City Subways' Key Performance Indicators to Improve Service Delivery and Operations. Issue 1 (January 2014) - Reddy, Alla; Lu, Alex; Boguslavsky, Mikhail; Levine, Brian
A balanced scorecard (BSC) is widely used in private industry and the public sector to monitor key performance indicators (KPIs) and to help achieve strategic outcomes. This concept is widely used in the transit industry for carrier–regulator contractual relationships and performance monitoring. After a fact-finding mission to Southeast Asia, New York City Transit (NYCT) adopted KPIs for continuous improvement of service delivery performance. Subway line-level KPIs based on BSC concepts were introduced in conjunction with a line general manager program and numerous initiatives for incremental performance management. After a reorganization that re-created functional departments—car equipment, stations, and rapid transit operations—BSC was applied at departmental levels and resulted in maintenance-oriented passenger environment survey (PES)-KPIs and operations-oriented service (S)-KPIs. Weightings of indicator sub components were assigned as a result of surveys of customer priorities. KPIs provided one number that represented overall performance, and they also made it possible to identify each subcomponent's contribution. The KPI design processes generated public feedback; this feedback prompted NYCT to tighten underlying performance standards. Today, PES-KPIs and S-KPIs are reported monthly to the Metropolitan Transportation Authority Board's NYCT Committee. Advantages of these indicators include high-level visibility and ease of communication, timely report availability, and detailed diagnostics. These factors, together with a reinvigorated competitive spirit between divisions triggered by reorganizations, resulted in a much more proactive organization focused on using performance scores to take corrective action. Wait assessment, the principal component of the S-KPI, improved 2.5% on the heavily crowded 1 through 6 lines in 2012 compared with 2011, even as ridership increased steadily systemwide.